(untitled) (Global Journal of Human-Social Science, 2019)
Terrorism is an ancient phenomenon as it comes from classical Antiquity However its global version only started in the last decades of the 19th century after the fall of Paris Commune and the murder of the Russian tzar Alexander the second Global terrorism is a phenomenon in which according to Rapoport we can consider four waves with religious one as its present phase This essay accepts the existence of several periods of global terrorism but it seeks to prove that the designations religious terrorism and Islamic terrorism are not entirely correct and they represent myths Besides it shows that these myths are based on two fallacies the clash of civilizations and the unity of Islam world and they are the origin of serious problems n ot only in the western world but also in the Islamic countries refusing to follow the Islamic law It is a ubiquitous problem because when a terrorist group is defeated it continues to shift away from a centralized command and control structure toward a more diffused model This strategy represents a severe threat because some terrorists choose a new battlefield while others return to the West but as radicalized as they were when they joined ISIS or any other terrorist group The world is facing a troubling phenomenon and its de-construction is essential for controlling a problem also related to identity